One health implications of fur farming - Warwick, Clifford; Pilny, Anthony; Steedman, Catrina; Grant, Rachel (Frontiers in Animal Science, 2023)
Fur farming involves the captive-breeding, rearing, and killing of between 85 -100 million animals annually for their pelts. The purpose of this report is to summarise key areas of significance and concern regarding fur farming, and discuss these matters and their one-health considerations. We conducted primary literature searches using Google Scholar and PubMed that focused on issues of animal welfare, zoonoses and public health, and environmental impacts of fur farming, and examined 280 reports. We identified that at least 15 species are farmed for fur across at least 19 countries. We found 16 categories of animal welfare concern (e.g., deprivation, stress, abnormal behaviours, insanitary conditions, forced obesity, and high morbidity and mortality), 18 reported endemic pathogens and diseases with confirmed or potential zoonotic and cross-species implications (e.g., bacterial n = 6, viral n = 5, and parasitic n = 7), and four main categories of environmental concern (e.g., greenhouse gas emissions, invasive alien species, toxic chemicals, and eutrophication) associated with fur farming. Despite numerous efforts to systematically monitor and control animal welfare at fur farms, practices continue to fail to meet normal scientific principles and models used in other animal welfare situations. In our view, limited available data does not currently indicate that fur farms are major sources of zoonotic epidemics and pandemics. The environmental problems caused by fur farming are significant, and relate mainly to invasive species, toxic chemical release and eutrophication of water bodies. We offer some recommendations for monitoring and controlling particular fur farming practices, in line with many governments and other investigators we conclude that inherent problems are essentially unresolvable and advocate complete prohibitions on the sector.